1999
DOI: 10.1128/mcb.19.6.4311
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Tristetraprolin Binds to AU-Rich Elements and Promotes the Deadenylation and Destabilization of Tumor Necrosis Factor Alpha mRNA

Abstract: Mice deficient in tristetraprolin (TTP), the prototype of a family of CCCH zinc finger proteins, develop an inflammatory syndrome mediated by excess tumor necrosis factor alpha (TNF-␣). Macrophages derived from these mice oversecrete TNF-␣, by a mechanism that involves stabilization of TNF-␣ mRNA, and TTP can bind directly to the AU-rich element (ARE) in TNF-␣ mRNA (E. Carballo, W. S. Lai, and P. J. Blackshear, Science 281:1001-1005, 1998). We show here that TTP binding to the TNF-␣ ARE is dependent upon the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
736
3
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 685 publications
(773 citation statements)
references
References 46 publications
29
736
3
5
Order By: Relevance
“…Nuclear localization of TTP in normal and stimulated cells is very minimal, with a high abundance in dividing cells (3). The localization of TTP primarily in the cytosol is in agreement with previous studies using THP-1 myelomonocytic cells (5,38), mouse tissues and cells (3), and GFP-tagged TTP in transfected cells (7). It is known that in response to mitogen stimulation, TTP is able to shuttle rapidly from the nuclei to the cytosol in NIH/ 3T3 mouse fibroblasts (39), and that the extent of cytoplasmic localization of TTP is also increased by association with 14-3-3 protein (25).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nuclear localization of TTP in normal and stimulated cells is very minimal, with a high abundance in dividing cells (3). The localization of TTP primarily in the cytosol is in agreement with previous studies using THP-1 myelomonocytic cells (5,38), mouse tissues and cells (3), and GFP-tagged TTP in transfected cells (7). It is known that in response to mitogen stimulation, TTP is able to shuttle rapidly from the nuclei to the cytosol in NIH/ 3T3 mouse fibroblasts (39), and that the extent of cytoplasmic localization of TTP is also increased by association with 14-3-3 protein (25).…”
Section: Discussionsupporting
confidence: 91%
“…Full-length TTP was expressed as a His-tagged protein (His-hTTP) in HEK293 cells. This cell line does not have detectable endogenous TTP mRNA (7). Cells were transiently transfected with pHis-hTTP plasmids encoding the wildtype, S186A, and T271A proteins, using the calcium phosphate precipitation method as described previously (7).…”
Section: Expression Of Ttp In Transfected Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…18 TTP is critically implicated in inflammation and is a member of zinc finger proteins that bind to AREs and destabilize mRNAs of tumor necrosis factor (TNF-␣). 19 However, TTP knockout causes a severe inflammatory syndrome in vivo, 20 and it is possible that the effects of TTP are countered by HuR. 21 Our previous data showed that LPS-enhanced TLR4 expression in human aortic smooth muscle cells (HASMCs) is mediated by mRNA stabilization, although we have not yet clarified whether RNA-binding proteins are involved in this process.…”
Section: See Page 2582mentioning
confidence: 99%
“…The CCCH-type zinc-finger motifs have been shown to be required for ZAP to bind the target RNA (Guo et al, 2004). Similar zinc-finger motifs also exist in tristetraproline (TTP) (DuBois et al, 1990), which specifically targets the AU-rich element (ARE) often found in the 3' untranslated regions of cytokines, growth factors and proto-oncogenes (Lai et al, 1999(Lai et al, , 2000Blackshear, 2002;Carrick et al, 2004;Barreau et al, 2005), and characterized by the AUUUA motif. These results suggest that sequence-specific interaction between ZAP and RNA is important for ZAP to bind the RNA.…”
Section: Discussionmentioning
confidence: 99%